Impacts of Supplemental Feeding on Sunbird-Pollination Systems in Young Fynbos Varies with Floral Abundance - Asekho Mantintsilili; Sjirk Geerts; Colleen L. Seymour; Anina Coetzee (Environmental Management, 2025)
Supplementary sugar-water feeding offers nectarivorous birds a source of spatially concentrated food, as opposed to the dispersed food available in flowers. This could impact bird visits to native flowers and alter plant-bird mutualisms, particularly in young post-fire vegetation. This study examined the effects of sugar-water feeders on nectarivorous birds and their plant mutualists in young (burned 18 months previously) and transitional vegetation (burned 5 years previously). A supplementary feeding experiment was conducted at Grootbos Private Nature Reserve in South Africa, using sugar-water feeders when floral abundance was low (winter) and high (spring). We compared bird abundance and visitation rates to flowers before, during, and after feeder presence in both seasons. The use of sugar-water feeders by nectarivorous birds was inversely related to floral abundance, with 679 bird visits (6.94 ± 1.40 bird visitation rate per hour) to feeders in winter and only 90 visits (0.41 ± 0.16 visitation rate per hour) during spring. Bird visits were higher at flowers than at sugar-water feeders, in both seasons. Sugar-water feeders did not influence the visitation rate of sunbirds to flowers in both seasons, contrasting with findings from areas abutting suburbia, suggesting that feeder influence on bird visitation rate may not be apparent in areas with no history of sugar-water feeders. We find that low numbers of feeders do not necessarily compete with natural nectar resources but may instead provide birds with an additional food source, particularly when floral resources are low.